Concepts in Middle Kingdom funerary culture : proceedings of the Lady Wallis Budge anniversary symposium held at Christ's College, Cambridge, 22 January 2016 - Nyord, Rune, (Culture and History of the Ancient Near East, 2019)
Concepts in Middle Kingdom Funerary Culture presents a collection of archaeological and philological papers discussing how ancient Egyptians thought, and modern scholars may think, about Egyptian funerary practices of the early 2nd millennium BCE. Targeting the concepts used by modern scholars, the papers address both general methodological questions of how concepts should be developed and used and more specific ones about the history and presuppositions behind particular Egyptological concepts. In so doing, the volume brings to the fore occasionally problematic intellectual baggage that have hindered understanding, as well highlighting new promising avenues of research in ancient Egyptian funerary culture in the Middle Kingdom and more broadly.